A Spiral Graphene Framework Containing Highly Ordered Graphene Microtubes for Polymer Composites with Superior Through‐Plane Thermal Conductivity. Issue 3 (19th December 2021) - Gong, Jinrui; Tan, Xue; Yuan, Qilong; Liu, Zhiduo; Ying, Junfeng; Lv, Le; Yan, Qingwei; Chu, Wubo; Xue, Chen; Yu, Jinhong; Nishimura, Kazuhito; Jiang, Nan; et al.
Comprehensive Summary: As the power density of electronic devices increases, there has been an urgent demand to develop highly conductive polymer composites to address the accompanying thermal management issues. Due to the ultra‐high intrinsic thermal conductivity, graphene is considered a very promising filler to improve the thermal conductivity of polymers. However, graphene‐based polymer composites prepared by the conventional mixing method generally have limited thermal conductivity, even under high graphene loading, due to the failure to construct efficient heat transfer pathways in the polymer matrix. Here, a spiral graphene framework (SGF) containing continuous and highly ordered graphene microtubes was developed based on a modified CVD method. After embedding into the epoxy (EP) matrix, the graphene microtubes can act as efficient heat pathways, endowing the SGF/EP composites with a high through‐plane thermal conductivity of 1.35 W·m −1 ·K −1 at an ultralow graphene loading of 0.86 wt%. This result gives a thermal conductivity enhancement per 1 wt% filler loading of 710%, significantly outperforming various graphene structures as fillers. In addition, we demonstrated the practical application of the SGF/EP composite as a thermal interface material for efficient thermal management of the light‐emitting diode (LED). Abstract :